Salidroside targets the Notch1/Hes5 axis to reconstruct the molecular innate immune–vascular network and correlates with repair after ischemic stroke - Zeng, Jing; Huang, Xiaohua; Zeng, Jingyi; Huang, Qi; Song, Wenyi; Xie, Youfeng; Liang, Guining; Wei, Qingyan; Lan, Yating; Zou, Donghua; Li, Rongjie; Gu, Lian (Frontiers in Immunology, 2026)
BackgroundIschemic stroke (IS) induces profound dysregulation of the neuro–molecular innate immune–vascular network, yet the molecular immune states and regulatory mechanisms of key cellular subpopulations remain insufficiently defined. Although traditional Chinese medicine (TCM) exhibits multi-target immunomodulatory potential, its cell-type and cell-state–specific actions within the ischemic brain microenvironment at single-cell resolution remain unclear.MethodsSingle-cell RNA sequencing was used to construct a cellular atlas of the ischemic mouse brain, followed by integrative bioinformatic analyses to characterize innate immune–related neural cell subpopulations and their regulatory networks. Network pharmacology and molecular docking were applied to identify salidroside (SAL), a major active compound of Rhodiola, and predict its potential molecular targets. In vivo experiments were performed to validate cellular and molecular changes associated with SAL treatment.ResultsIn a mouse model of IS, ischemic injury induced pronounced imbalances across multiple immune and glial cell subpopulations. A transcriptionally defined Notch1+ Hes5+ astrocyte (ASC), enriched for progenitor-like and reparative gene signatures, was markedly reduced after ischemic injury, whereas reactive SerpinA3N+ ASC and pro-inflammatory Sell+ microglia (MG) were expanded. Additionally, alterations were observed in immune-regulatory cell populations, including Cxcl12+ endothelial cells (ECs) and Gpr34+ Ptgs1+ MG. In vivo validation showed that SAL treatment was associated with modulation of Notch1/Hes5 signaling in ASC, reduced reactive ASC features, and partial normalization of ECs alterations, accompanied by changes consistent with attenuated neuroimmune activation. These effects coincided with altered intercellular communication, particularly involving NOTCH signaling.ConclusionsThis study provides single-cell–level insights into innate immune microenvironment remodeling following IS and identifies a Notch1+ Hes5+ ASC subpopulation with transcriptional features associated with reparative-related programs and responsiveness to SAL. The findings suggest that SAL-associated neuroprotection was accompanied by modulation of ASC states and immune–glial communication, highlighting the potential of SAL-associated immunoregulatory effects at the single-cell level in IS.